2010
DOI: 10.1071/sh10075
|View full text |Cite
|
Sign up to set email alerts
|

Closing editorial: processes, opportunities and challenges after introduction of human papillomavirus vaccine

Abstract: This issue of Sexual Health has reflected on processes, opportunities and challenges that human papillomavirus (HPV) vaccines have created for the prevention of cervical cancer and other HPV-related diseases. Having been in development for over a decade, it is notable how rapidly HPV vaccines have been implemented in developed countries worldwide after registration for use. It is fair to note that this reflects a wave of enthusiasm for a preventive strategy for cervical cancer which, unlike cervical cytology s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The HPV vaccine has progressed relatively rapidly through research and development and commercial availability [49]. Four KIs, primarily from international perspectives, attributed this success to cervical cancer advocacy groups, and suggested that advocacy will continue to play a key role in influencing implementation and policymakers:

“ I think cervical cancer advocacy has been quite good…they’ve been able to mobilize themselves quite effectively and the vaccine certainly has moved through its systems of development quite fast ” (KI-E).

…”
Section: Political Barriersmentioning
confidence: 99%
“…The HPV vaccine has progressed relatively rapidly through research and development and commercial availability [49]. Four KIs, primarily from international perspectives, attributed this success to cervical cancer advocacy groups, and suggested that advocacy will continue to play a key role in influencing implementation and policymakers:

“ I think cervical cancer advocacy has been quite good…they’ve been able to mobilize themselves quite effectively and the vaccine certainly has moved through its systems of development quite fast ” (KI-E).

…”
Section: Political Barriersmentioning
confidence: 99%